Institutions and Economic Growth in Sub-Saharan African Countries: The Effect of Investment Climate Quality (International Journal of Scientific Research and Management (IJSRM), 2020)
This paper assesses the impact of investment climate quality on economic growth for a sample of 21 countries in Sub-Saharan Africa (SSA), over the period 1996-2014. The investment climate is measured simultaneously by individual components and composite indices, in order to capture both its global and specific effects, with a view to possibly identifying the most determining factors in the economic growth of SSA countries. In addition, in order to verify the robustness of our results, two composite indices of investment climate were constructed using the Principal Component Analysis method, with variables from two main databases (the World Governance Indicators database of World Bank and the International Country Risk Guide database). By using fixed and random effects models based on Hausman test results, we generally find that investment climate is a major determinant of economic growth in the countries of the SSA of the study sample. This result is valid regardless of the composite index or the individual component considered. Fight against corruption, protection of private property rights, efficiency of government, the quality of bureaucracy and regulation appear to be the most decisive components in accelerating economic growth for the sample of country considered.